αLβ2 integrin is indispensable for CD8+ T-cell recruitment in experimental pancreatic and hepatocellular cancer - Takeichi, Takayuki; Mocevičius, Paulius; Deduchovas, Olegas; Salnikova, Olga; Castro Santa, Edward; Büchler, Markus W.; Schmidt, Jan; Ryschich, Eduard (International journal of cancer, 2012)
Recruitment of activated leukocytes from peripheral blood into the tumor tissue is a crucial step of the immune response, which is controlled by the interaction between specific adhesion molecules such as endothelial ICAM-1 and leukocyte β2-integrins. Although attenuated expression of adhesion molecules on tumor endothelium has been proposed to represent a mechanism, which suppresses the intratumoral leukocyte infiltration, the relevance of adhesion molecules for leukocyte recruitment in tumor tissue is poorly understood. The present study is the first investigation of the role of ICAM-1 and β2-integrins in leukocyte recruitment in pancreatic and hepatocellular cancer in vivo, which was studied using knockout mice, intravital time-lapse microscopy and immunohistochemistry. We found that tumor tissue of both pancreatic and hepatocellular cancer was infiltrated with numerous active lymphoid and myeloid leukocytes, although the leukocyte extravasation rate in tumor blood vessels was very low. The knockout of LFA-1 (also known as αLβ2 integrin) strongly suppressed recruitment of CD8+ T cells whereas no significant differences of leukocyte adhesion and infiltration were found in ICAM-1−/− and Mac-1−/− mice. Analysis of the interstitial leukocyte migration demonstrated that intratumoral leukocytes used haptokinetic type of migration, however, no significant differences of leukocyte migration between any knockout strains were found. We concluded that leukocyte recruitment in pancreatic and hepatocellular cancer is a slow-going process whose dynamics clearly contrasts to a high-speed leukocyte recruitment during acute inflammation. In contrast to acute inflammatory reaction, only LFA-1 controls recruitment of CD8+ T-cells in both pancreatic and hepatocellular cancer, whereas ICAM-1 and Mac-1 are dispensable.